(untitled) (Nepal Journal of Health Sciences, 2025)
Introduction: The common terminal molar relations are flush terminal, mesial step and distal step. Along with that the normal features of primary dentition are physiological spaces, flush terminal plane, low overjet and overbite and ovoid arch form. Variations in these features would be carried to the succeeding permanent dentition in a more distinct form. Objective: The study aimed to assess the occlusal characteristics of primary dentition in preschoolers visiting one of the tertiary hospitals in Nepal. Methods: An analytical cross-sectional study was conducted in pre-schoolers selected by convenience sampling method. Occlusal characteristics of primary dentition such as molar relation, canine relation, overbite, overjet, crowding and cross bite were recorded. Results: The most common type of molar relation was flush terminal plane (50.8- 51.2%) followed by mesial step (48.1- 48.5%) and distal step (0.4 - 1.2%). Canine relation was predominantly Class I (92-93%) followed by class II (5-6%) and class III. The prevalence of crowding, ideal overjet, ideal overbite, physiological spaces was 9.6%, 79.6%, 60.8%, 60% respectively. The median overjet and overbite were identical across the compared groups at 2 mm (1–2 mm) and 2 mm (2-3 mm) respectively. Conclusions: The most common type of occlusal characteristics were flush terminal plane and class I canine relation. This may be attributed to balanced growth of craniofacial region and anteroposterior arch in most of the children suggesting lower probability of malocclusion in permanent dentition.